Base sequence-specific interactions of operator DNA fragments with the lambda-cro repressor coupled with changes in their conformations. - Lee, S J (1987)
The mechanism of interaction of the operator DNA with the lambda-cro repressor protein was investigated using proton n.m.r. and photo CIDNP. Three kinds of DNA duplexes, the lambda-OR3 17-mer, phi80-OR2 19-mer and CRP binding site 22-mer, were prepared, and all of their imino proton resonances of the complexes with lambda-cro were assigned to individual base pairs. By monitoring the assigned signals of the DNA fragments and lambda-cro, it was found that in the complex of lambda-cro with lambda-OR3, two subunits of the cro dimer bind to the right and left halves of the OR3, respectively, and the bidentate binding induces a structural distortion in the middle of the 17-mer. lambda-cro itself also undergoes a conformational change including loosening of the dimeric form. In the complex of lambda-cro with phi 80-OR2, which has a 6-bp sequence common to that of lambda-OR3, one subunit of the cro dimer seems to bind specifically to the common part. However, there is only a slight conformational change in the cro dimer. In the mixture of the CRP binding site 22-mer and lambda-cro, soft contact without any conformational change was observed between them.